The secret keepers - Stewart, Trenton Lee (Little, Brown and Company, 2016)
Reuben discovers an antique watch and soon realizes that it holds special power. And as one secret leads to another, Reuben and his friends Penny, Jack, and Mrs. Genevieve must outwit the sly villain known as The Smoke to save their city from a terrible fate.